Apuração de haveres ou o pacto autoficcional - Ewerton Martins Ribeiro (2021)
On this thesis – written while articulating the theoretical discourse and literary performance – I propose a definition to the notion of autofictional pact. This is a definition for the singularity of the reading contract that a literary work of autofiction, if considered conceptually, proposes/imposes onto its reader, alongside the way this contract operates and its implications. I fulfill this task making a distinction between the autofictional pact and the reading contracts which novels and autobiographies tout court establish with their readers, but seek to set this new pact not in opposition to the roman and autobiographical pacts, but through, between and beyond them, in a trans disciplinary approach of the matter, analyzing it through the lenses of complexity, logic of the third included and the levels of reality. In order to establish this notion of autofictional pact in its complex implications, I set, first, the concept of autofiction — doing so under the perspective of complexity, as established by Edgar Morin and through a recuperation of the genealogy of term/concept, from a critical reflection of how it was handled and appropriated in the following decades since its inception in 1977 and a conceptual investigation of its most recent manifestations. Finally, I deal with the pervasive character of the autofictional pact in the contemporary zeitgeist, demonstrating how something that, instead of circumvent only the literary or artistic means, sprawls out through diverse fields of the contemporary human experience — thus reconfiguring it in the terms of the aesthetic regime of the arts established by Jacques Rancière.